2022
DOI: 10.1021/acsaelm.1c01269
|View full text |Cite
|
Sign up to set email alerts
|

Wearable and Biocompatible Blood Oxygen Sensor Based on Heterogeneously Integrated Lasers on a Laser-Induced Graphene Electrode

Abstract: Wearable electronics or epidermal electronics have attracted growing interest for their expansion into markets as health monitors and for biological applications. However, a key obstacle lies in the light source and the optical path change caused by the deformation and displacement in the measurement. In this work, we demonstrated a wearable and biocompatible blood oxygen monitor by using heterogeneously integrated vertical cavity surface emitting lasers (VCSELs) and a Si photodetector (PD) on a Au-laser-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Similar kinds of photonic devices based on organic and inorganic and visible to infrared photodetectors are also reported to measure arterial pulse wave. 151–157…”
Section: Recent Developments In Bp Measurement Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar kinds of photonic devices based on organic and inorganic and visible to infrared photodetectors are also reported to measure arterial pulse wave. 151–157…”
Section: Recent Developments In Bp Measurement Technologiesmentioning
confidence: 99%
“…Similar kinds of photonic devices based on organic and inorganic and visible to infrared photodetectors are also reported to measure arterial pulse wave. [151][152][153][154][155][156][157] Han et al presented a flexible polymer sensor for dynamic physiological signals. 147 The sensor was fabricated using P(VDF-TrFE-CFE) copolymer and PET substrate via a spincoating technique (Fig.…”
Section: Technologies Towards Bp Measurementmentioning
confidence: 99%
“…For example, single-layer or few-layer graphene atoms are thin and exhibit high flexibility. Graphene-based devices can be bent and cycled many times without affecting their performance by placing them on flexible substrates [ 12 , 155 ]. Recently, it was found that the special 3D structure of graphene heterojunction PDs promotes device functions that cannot be realized by planar geometric structures.…”
Section: Application Of Pds In Flexible Wearable Electronicsmentioning
confidence: 99%
“…Oxygen is a crucial element for the proper functioning of the human body. It plays a key role in several reactions in the fields of medicine and chemistry. , Oxygen exists in diverse forms in nature, including the form of dissolved oxygen, , which is the oxygen exchanged between a solution and the atmosphere or that dissolved in water through chemical reactions. , It holds significant importance as an indicator in aquaculture. Maintaining an appropriate oxygen level is very important to aquatic life; both excessively high and low levels can be very dangerous. For instance, fish may suffocate and die if the dissolved-oxygen level falls below 4 mg/L .…”
Section: Introductionmentioning
confidence: 99%